Efektivitas Pembinaan Ibadah dan Keagamaan Bagi Narapidana Muslim di Lapas Amurang - Sahari; Edi Gunawan (Al-Mizan (e-Journal), 2021)
This study aims to determine how effective worship and religious guidance is applied by the Class III Penitentiary of Amurang to Muslim prisoners. The guidance of worship is an effort and action carried out by a person to assist in understanding an individual or group to grow awareness to achieve good relations between humans and God and fellow creatures. This study uses a qualitative approach, with the research subjects being Muslim inmates and counselors at the Ministry of Religion. The method of collecting data is through observation, interviews, and documentation that explains the activities of worship development for Muslim inmates at the Penitentiary of Amurang. The results found that worship development for Muslim prisoners in the Penitentiary of Amurang was carried out as an effort to increase awareness of the importance of congregational prayers at the time of the Zuhr prayer, Asr prayer, Maghrib prayer, Isha prayer, and Friday prayer, except for the Fajr prayer carried out in their respective blocks. Streamlining reciting after every Zuhr and Asr prayers, prayer practices on Wednesdays, voluntary fasting on Mondays and Thursdays, and Ramadan, lecture and deprecate practices on Fridays. With regular worship services, the inmates' understanding of worship increases, improves personality, creates awareness, patience, and a sense of kinship. Constraints faced are the lack of facilities and infrastructure, the lack of officers who have religious knowledge, the lack of role models from prison employees in terms of carrying out worship.